Exploring the expansion of patent information based on linked data. (2015) - Park, Ok Nam
With more emphasis on the significance of intellectual property rights, it has become important to secure intellectual property rights in order for firms and individuals to achieve success. In spite of the importance of comprehensive and efficient patent information search, keyword-based search systems and different patent classifications are all factors that limit efficient patent search. This study presents an ontology modelling as a basic step to build a methodical system for patent information. The FRBR model was adopted to divide patent information into patent bibliography, agent and classification, and built ontology based on RDF/OWL. The study also presents an expanded model for patent information system by linking patent-related information.